The Roles of Different News Media Use and Press Freedom in Education Generated Participation Inequality: An Eight Country Comparative Analysis. Issue 3 (3rd July 2019) - Ahmed, Saifuddin; Cho, Jaeho
Abstract : This eight-nation comparative study adopts a multi-modal analytical approach in investigating education driven stratification in political participation and the simultaneous roles of various media (print newspaper, television, radio, and social media) and press freedom in influencing this inequality. The findings suggest that informational use of social media, print newspaper, and radio increases the likelihood of participation, but consuming television news inhibits participation. Furthermore, social media use, like radio and television use, exacerbates education-generated inequality. Press freedom as a socio-political factor reinforces the role of the television, print newspaper, and social media in participation inequality. Theoretical and policy implications are discussed.